A LABORATORY STUDY OF VIBRATION EFFECT FOR DEFORMABLE DOUBLE-POROSITY SOIL WITH DIFFERENT MOISTURE CONTENT (Malaysian Journal of Civil Engineering, 2018)
Earthquake vibration is a natural disaster that needs to be addressed in ensuring the geo-environment is sustainably secure. A physical laboratory model was conducted to characterize the phenomena of vibrated deformable double-porosity under different moisture content. The double-porosity soil characteristic is formed by aggregating kaolin soil with 32% and 33% moisture content. A vibrating table and seismic accelerometer were installed on soil sample in order to vibrate the whole acrylic soil column to get the peak table acceleration and peak specimen surface acceleration of the soil sample. The results show that the acceleration response analysis for the sample with 32% moisture content has caused sample dis-amplification shaking, while the sample with 33% moisture content has caused the sample amplification shaking and re-compact process to occur due to strong vibration. It was recorded that both vibrated samples have soil structure rearrangement and multi-porosity characteristics identified as problematic double-porosity soil expected to contribute to the speed of liquid penetration. In addition, the microscope result shows both samples have crumbs with diameter less than 0.5cm, which is considered to have granular soil structure.Thus, both samples displayed the characters of soil liquidity as the moisture content for both samples is close to kaolin soil liquid limit at 41%, and granules started to disintegrate at the moisture content of 34%.